2014
DOI: 10.1371/journal.pone.0082716
|View full text |Cite
|
Sign up to set email alerts
|

Traceless Bioresponsive Shielding of Adenovirus Hexon with HPMA Copolymers Maintains Transduction Capacity In Vitro and In Vivo

Abstract: Capsid surface shielding of adenovirus vectors with synthetic polymers is an emerging technology to reduce unwanted interactions of the vector particles with cellular and non-cellular host components. While it has been shown that attachment of shielding polymers allows prevention of undesired interactions, it has become evident that a shield which is covalently attached to the vector surface can negatively affect gene transfer efficiency. Reasons are not only a limited receptor-binding ability of the shielded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…268 Transduction with pHPMA copolymer coatings was shown to be maintained not only in cell cultures but also in vivo in mouse models. 267, 269 PEG has also been shown to be an effective polymer for shielding 270 and retargeting. 271 As an improvement to simple PEG coatings, complexation with copolymers of PEG and PEI resulted in the ability to transduce CAR-negative NIH 3T3 cells, with the added benefit of less toxicity compared to PEI alone.…”
Section: Applications Of Virus-based Particlesmentioning
confidence: 99%
“…268 Transduction with pHPMA copolymer coatings was shown to be maintained not only in cell cultures but also in vivo in mouse models. 267, 269 PEG has also been shown to be an effective polymer for shielding 270 and retargeting. 271 As an improvement to simple PEG coatings, complexation with copolymers of PEG and PEI resulted in the ability to transduce CAR-negative NIH 3T3 cells, with the added benefit of less toxicity compared to PEI alone.…”
Section: Applications Of Virus-based Particlesmentioning
confidence: 99%
“…Although our data indicated that the CKS17 peptide insertion into HVR5 reduced hepatocyte transduction in vivo while increasing uptake into early pancreatic cancer cells and hPSCs in vitro , it is presently unclear whether this will translate to an enhanced anti-tumor activity in vivo . Complementary strategies to further improve bioavailability could be used such as site-specific genetic-chemical modification (using polymers such as polyethylene glycol or N-(2-hydroxypropyl)methacrylamide) [ 18 , 66 68 ] or engineering of capsid proteins to further reduce unwanted interactions with non-cellular or cellular blood components or with the reticulo-endothelial system (Kupffer cells, LSECs) [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies utilizing 'bioresponsive' polymers (e.g. polymers that were cleavable in acidic conditions) to shield Ad were investigated [90,91]. After intratumoral injection, Carlisle et al [91] showed increased levels of infection with a bioresponsive PHPMA coating when compared with an irreversible PHPMA Ad5 coating.…”
Section: Chemicalmentioning
confidence: 99%